Arbuscular Mycorrhizal Colonization Enhances Biochemical Status and Mitigates Adverse Salt Effect on Two Legumes - Promita DATTA; Mohan Vinayak KULKARNI (Notulae Scientia Biologicae, 2014)
</style> Symbiotic association between arbuscular mycorrhizal (AM) species and host plant roots improves plant growth and protects them from several abiotic stress factors. In the present study, the effect of Glomus mosseae and Glomus fasciculatum as an individual inoculation and in combination was studied on two legumes (Glycine max and Cyamopsis tetragonoloba) under soil salinity stress gradient [1.04 (control) to 8.26 dS/m]. Individual and co-inoculation of both the AM fungi alleviated adverse salt effect, with improvement in plant dry weight matter and biochemical parameters. However, these two isolates worked better in combination with respect to higher accumulation of soluble carbohydrate, reducing sugar, protein, proline concentration etc. C. tetragonoloba showed better response as compared to G. max in relation to improvement in nutritional profile under salt stress after AM treatment. As compared to non-mycorrhizal counterparts, co-inoculation with G. mosseae and G. fasciculatum in C. tetragonoloba enhanced total chlorophyll (14.83% at soil salinity of 3.78 dS/m), soluble carbohydrate (17.26% at soil salinity of 5.94 dS/m), proline (8.79% at soil salinity of 3.78 dS/m) while exposed to different soil salinity levels. Also, co-colonization with both the isolates showed more root colonization (%) and may be responsible for the better effect in salt stress alleviation. Electrolyte leakage of mycorrhizal plants was lowered at soil salinity gradient of 2.10 to 8.26 dS/m and hence, maintained membrane stability. These two isolates can be utilized as bio-inoculant in alleviation of adverse salt effect in soil in association with the two test legume plants.